THE IMPACT OF THE ASSOCIATION AGREEMENT BETWEEN THE EUROPEAN UNION AND UKRAINE ON MUTUAL TRADE AND UKRAINIAN PORTS CARGO - Туляков, Вячеслав Олексійович; Туляков, В. О.; Туляков, Вячеслав Алексеевич; Tuliakov, Viacheslav O.; Tulyakov, Vyacheslav A.; Alekseievska, Halyna; Yakubovskiy, Sergey (Hrčak, 2023)
European integration is a key priority of Ukraine’s foreign policy. The main strategic document of interaction between Ukraine and the EU is the Association Agreement, the most important component of which is the Deep and Comprehensive Free Trade Area (DCFTA). The article presents the results of studying the dynamics, state, and structure of Ukraine’s foreign trade with the countries of the European Union before the war. It was revealed that Ukraine continues to establish itself in international markets as a key player-exporter of agricultural products. It is emphasized that Ukraine is an important political and trade partner of the EU. It is demonstrated that both sides are striving for even greater convergence of relations that go beyond simple cooperation, towards gradual economic integration and deepening political cooperation. Despite the prospects for the further development of trade relations, which improved in 2021, 2022 made adjustments. In particular, the aggression of Russia against Ukraine had a negative impact on trade flows both in Ukraine and in the whole world. Despite this, since the beginning of the war in Ukraine, there has been an increase in merchandise exports to the EU, which because the blocking of seaports does not allow Ukrainian companies to directly deliver goods to Asia, Africa, and America, and they are forced to do this through the EU countries. As a result, after the outbreak of a full-scale war between Russia and Ukraine, the EU further strengthened the position of Ukraine’s main trading partner.
Tuliakov, V., Alekseievska, H. & Yakubovskiy, S. THE IMPACT OF THE ASSOCIATION AGREEMENT BETWEEN THE EUROPEAN UNION AND UKRAINE ON MUTUAL TRADE AND UKRAINIAN PORTS CARGO. InterEULawEast. 2023. Vol.10, № 1, pp. 1-19. https://doi.org/10.22598/iele.2023.10.1.1
Keywords: EU countries; association agreement; free trade area; export; import; port cargo; the war of Russia against Ukraine; країни ЄС; угода про асоціацію; зона вільної торгівлі; експорт; імпорт; портові вантажі; війна Росії проти України